Epigenetik dan Penuaan (Aging): Peluang Intervensi Molekuler untuk Hidup Sehat Lebih Lama - Dwi Lunarta Docterina Sutanti Siahaan; Hadyanto Lim (Majalah Ilmiah METHODA, 2025)
Aging is a complex biological process characterized by a decline in cellular function and increased susceptibility to degenerative diseases. In recent decades, research has shown that epigenetic modifications—such as DNA methylation, histone modification, and regulation by non-coding RNAs—play a key role in the aging process. These changes influence gene expression without altering the DNA sequence and contribute to cellular damage, chronic inflammation, and tissue dysfunction. As scientific understanding advances, various epigenetic-based molecular interventions have emerged, including epigenetic reprogramming, senolytic therapies, and pharmacological and lifestyle approaches targeting epigenetic mechanisms. Although challenges remain in terms of safety, specificity, and clinical applicability, these approaches offer promising potential for extending healthspan and improving quality of life in later years.